P184 Calculation of conductive inhomogeneity in children with severe cf lung disease: which method works?. (15th November 2016) - Verger, N; Arigliani, M; Raywood, E; Duncan, JA; Bush, A; Aurora, P
Abstract : Introduction: Convection Dependent Inhomogeneity (CDI, a measure of ventilation inequality among larger lung units) quantified by Scond cannot be assessed in subjects with severe ventilation inhomogeneity (VI) as assumptions underlying the calculation are invalid; an alternate index that has been suggested is Scond. 1 Aim: To compare these two methods of CDI assessment in CF children Methods: Children with cystic fibrosis (CF; 67) and healthy controls (61) performed multiple breath washout with sulphur hexaflouride measured using mass spectrometry. Scond was calculated from 1.5 to 6 turnovers and Scond* from breath 2 to 3 turnovers. Results: All measures of VI were significantly higher for CF vs control, mean difference: LCI 4.0, Scond 0.054, Scond* 0.081. In CF, LCI correlated better with Scond* than Scond (See figure : correlation coefficient LCI vs. Scond* 0.75; LCI vs. Scond 0.42). If children with moderate-severe VI (LCI > 11) were excluded there was an improved correlation for both relationships (correlation coefficient LCI vs. Scond 0.83; LCI vs. Scond* 0.86). An asymptote for the Scond vs LCI relationship was at Scond 0.07 and Scond* 0.13. Conclusion: Scond* quantifies the mechanism of VI in moderate to severe lung disease, but it may reach asymptote in very severe VI. Reference: Verbanck. Respiratory Physiology & Neurobiology, 2013.